PENCITRAAN POLITIK PARTAI AMANAT NASIONAL (PAN) DI KABUPATEN LABUHAN BATU SELATAN TAHUN 2009-2014 - Anang Anas Azhar (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
This study examines the political imagery of the National Mandate Party (PAN) DPD Nasonal Mandate Party (PAN) in South Labuhan Batu regency in 2009-2014. Political imagery aims to convince and influence voters by instilling a positive opinion to the public about the party being imaged. This study used a qualitative approach disign, with descriptive methods, through data collection interviews, observation and documentation. The results of this study reveal: First, to increase the political imaging DPD PAN South Labuhan Batu 2009-2014, using the channel, mass communication, interpersonal communication, and outdoor communication. Secondly, PAN South Labuhan Batu imaging through the use of the newspaper medium, realize the flagship program in direct contact with the public interest, such as the consolidation of the party, cadres, atributisasi, socialization, and actions on the ground. The success of the PAN political imagery, seen from the success of South Labuhan Batu PAN won 11 seats in parliament South Labuhan Batu regency. Third, the political imaging models that do DPW PAN South Labuhan Batu most influential is the interpersonal communication, and the program featured real action PAN.